2018
DOI: 10.1159/000493043
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Potential of Circulating Long Non-Coding RNAs in Non Small Cell Lung Cancer

Abstract: Lung cancer is the leading cause of cancer-related mortality worldwide. Approximately 80% of lung cancer cases are non–small cell lung carcinoma (NSCLC). However current diagnostic and therapeutic modalities against NSCLC are ineffective due to incomplete understanding of molecular pathogenesis of NSCLC. Emerging evidence shows that long non-coding RNAs (lncRNAs) can function as biomarkers for diagnosis and prognosis. LncRNAs can control transcription, translation, and protein function via diverse mechanisms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 82 publications
(83 reference statements)
0
35
0
Order By: Relevance
“…Functional assays further showed that PART1 knockdown‐mediated anti‐proliferation, anti‐migration, and anti‐invasion effects were suppressed via JAK1 or JAK3 overexpression in NSCLC, in line with that of Wang et al Further xenograft tumor growth model of NSCLC also confirmed the antitumor genesis role of PART1 knocking down via inactivation of JAK‐STAT signaling pathway. Although a large number of lncRNAs are considered as diagnostic and prognostic markers as well as therapeutic targets for NSCLC, due to complicated pathogenesis of NSCLC, more molecular mechanisms involved in NSCLC need to be further explored. Moreover, the further study of PART1 on regulation of AS is still indispensable to be investigated via more elaborate animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Functional assays further showed that PART1 knockdown‐mediated anti‐proliferation, anti‐migration, and anti‐invasion effects were suppressed via JAK1 or JAK3 overexpression in NSCLC, in line with that of Wang et al Further xenograft tumor growth model of NSCLC also confirmed the antitumor genesis role of PART1 knocking down via inactivation of JAK‐STAT signaling pathway. Although a large number of lncRNAs are considered as diagnostic and prognostic markers as well as therapeutic targets for NSCLC, due to complicated pathogenesis of NSCLC, more molecular mechanisms involved in NSCLC need to be further explored. Moreover, the further study of PART1 on regulation of AS is still indispensable to be investigated via more elaborate animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is one of the cancers with high morbidity and mortality, which consists of more than 50 histological subtypes (1,2). Non-small cell lung cancer (NSCLC) is the dominant type, accounting for about 80% of lung cancers (3). The combination of conventional platinum chemotherapy and radiotherapy is the standard therapy for locally advanced unresectable NSCLC (4).…”
Section: Introductionmentioning
confidence: 99%
“…Five NSCLC datasets (GSE19804, GSE27262, GSE43458, GSE75037, GSE103512), including 308 tumor samples and 207 normal lung samples, were downloaded from GEO (https://www.ncbi.nlm.nih.gov/geo). The inclusion criteria for these datasets were as follows: (1) primary NSCLC histology; (2) no history of radiotherapy or chemotherapy; and (3) more than 50 pathological specimens on each chip. The GSE19804, GSE23066, and GSE27262 datasets were generated from the same detecting microarray platform ([HG-U133_Plus_2] Affymetrix Human Genome U133 Plus 2.0 Array), whereas the GSE43458, GSE75037, and GSE103512 data sets were…”
Section: Nsclc Transcriptome Microarray Datasetmentioning
confidence: 99%